Kerjasama Bilateral Indonesia-Tiongkok dalam Diplomasi Kesehatan di Masa Pandemi Covid-19 - Ida Susilowati; Anisa Nuryanti Affandi; Cut Jihan Raihana; Elsa Iqlima Az-Zahra (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
In 2019, the Covid-19 pandemic emerged and shook the world. The health industry is only one of several that could encounter difficulties if countries don't prepare for them. Countries' diplomatic efforts are counted on to address health issues during a pandemic. In this situation, Indonesian and Chinese officials are working to control disease outbreaks better. During the Covid-19 pandemic, Indonesia and China devised a health diplomacy strategy; this research seeks to outline such a strategy. Specifically, this study employs a qualitative research approach, focusing on descriptive analysis. China's support for the Public Health Cooperation Capacity initiative: Program on Public Health Emergency Preparedness Capacity (ROMPT) in dealing with the Covid-19 pandemic is highlighted, as is China's assistance in the form of medical equipment, cooperation in vaccine diplomacy, service in the state of advanced technology, and scientific research.Keywords: Pandemic Covid-19; Bilateral Cooperation; Health Diplomacy; Indonesia-China. AbstrakPada tahun 2019, pandemi Covid-19 muncul dan mengguncang dunia. Industri kesehatan hanyalah salah satu dari beberapa yang dapat menghadapi kesulitan jika negara tidak mempersiapkannya. Upaya diplomasi negara-negara diperhitungkan untuk mengatasi masalah kesehatan selama pandemi. Dalam situasi ini, pejabat Indonesia dan China bekerja sama untuk mengendalikan wabah penyakit dengan lebih baik. Di masa pandemi Covid-19, Indonesia dan China menyusun strategi diplomasi kesehatan; penelitian ini berusaha untuk menguraikan strategi tersebut. Secara khusus, penelitian ini menggunakan pendekatan penelitian kualitatif, dengan fokus pada analisis deskriptif. Dukungan China terhadap inisiatif Public Health Cooperation Capacity: Program on Public Health Emergency Preparedness Capacity (ROMPT) dalam menghadapi pandemi Covid-19 menjadi sorotan, begitu pula bantuan China berupa peralatan medis, kerja sama diplomasi vaksin, bantuan dalam bentuk teknologi canggih, dan penelitian ilmiah.Kata Kunci: Pandemi Covid-19; Kerjasama Bilateral; Diplomasi Kesehatan; Indonesia- Tiongkok.